The Influence Of Social Media, Lifestyle, And Environment On Student Consumptive Behavior - Marwiyati, Marwiyati; Elfida, Cut; Al Mizan, Muhammad Daniel; Raju, Mohd Jaisar (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2026)
Students often follow trends to gain recognition in their social environment, development of technology and social media has made access to consumption trends easier. This can encourage consumptive behavior, which becomes problematic if done excessively without considering needs and financial capability. This study analyzes the influence of social media, lifestyle, and environment on the consumptive behavior of students in Syiah Kuala District using a quantitative approach with 100 respondents. The results show that social media has no significant effect, while lifestyle and environment do have an effect. Simultaneously, the three variables influence consumptive behavior with a contribution of 55.3%, while the remaining 44.7% is influenced by other factors not examined in this study.